Адміністративно-правове регулювання обігу зброї, що має культурну цінність, у Республіці Білорусь - Чумак, В. В.; Chumak, V. V.; ORCID: http://orcid.org/0000-0002-6171-2250 (Вісник Харківського національного університету внутрішніх справ. - 2014. - № 2 (65). - С. 187-192, 2014)
Проаналізовано нормативно-правові акти, які регулюють обіг зброї, що має культурну цінність, у Республіці Білорусь. Встановлено порядок обігу і перелік видів зброї, що має культурну цінність у Республіці Білорусь. Зазначено, що колекціонування та експонування зброї, яка має культурну цінність, мають право здійснювати організації та громадяни Республіки Білорусь, які мають ліцензії на колекціонування та експонування зброї. Визначено перелік підрозділів, які здійснюють контроль за обігом на території Республіки Білорусь зброї, що має культурну цінність.

The regulations, that regulate the circulation of weapons that have cultural value in Belarus, are analyzed. A procedure for arms trafficking, that has cultural value in Belarus, is established. A list of weapons and ammunition, that has cultural value in Belarus, is established. It is stated, that a weapon, which has cultural value, include: weapons, which included a list of the State Historical and Cultural Values of the Republic of Belarus; weapon, that is in the Museum Fund of the Republic of Belarus; weapon, that is presented in the prescribed manner to the Department for the Protection of historical and cultural heritage and restoration of the Ministry of Culture of the Republic of Belarus to decide on its inclusion in the list of the State Historical and Cultural Values of the Republic of Belarus; weapons, that fall under the categories set out in the rules approved by the Council of Ministers of the Republic of Belarus the categories of cultural property export them from the Republic of Belarus is limited. It is set, that collecting and exhibiting weapons, that have cultural value, can be done by organizations and citizens of Belarus, who are licensed to collecting and exhibiting these types, styles, models, weapons, issued by Ministry of Interior of the Republic of Belarus in accordance with legislation. It is stated, that accounting, storage, transportation, transportation of weapons that have cultural value, are carried out in a general way, which is set by the legislation of the Republic of Belarus for registration, storage, transportation, transportation of weapons. This article states, that the removal of weapons, that have cultural value, is carried out in a general way, which is set by law of the Republic of Belarus to extract weapons. The list of departments, that exercise control over the circulation of the Republic of Belarus of arms, that has cultural value, is set.

Проанализированы нормативно-правовые акты, регулирующие оборот оружия, имеющего культурную ценность, в Республике Беларусь. Установлен порядок оборота и перечень видов оружия, имеющего культурную ценность, в Республике Беларусь. Указано, что коллекционирование и экспонирование оружия, имеющего культурную ценность, имеют право осуществлять организации и граждане Республики Беларусь, обладающие лицензиями на коллекционирование и экспонирование оружия. Определён перечень подразделений, осуществляющих контроль за оборотом на территории Республики Беларусь оружия, имеющего культурную ценность.
Administrative and legal regulation of weapons that have a cultural value in Belarus
Административно-правовое регулирование оборота оружия, имеющего культурную ценность, в Республике Беларусь
Чумак, В. В. Адміністративно-правове регулювання обігу зброї, що має культурну цінність, у Республіці Білорусь / В. В. Чумак // Вісник Харківського національного університету внутрішніх справ. - 2014. - № 2 (65). - С. 187-192.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; ліцензійно-дозвільна система; Білорусь; обіг зброї; Республіка Білорусь; licensing system; Belarus Republic; turn; лицензионно-разрешительная система; Беларусь; оборот оружия; оружие; Республика Беларусь; оружие, имеющее культурную ценность; weapons that have a cultural value; зброя, що має культурну цінність